MUNICIPAL POLICE: THE POTENTIAL IN THE CONTEXT OF IMPLEMENTING THE EXECUUTIVE BODIES OF LOCAL SELF-GOVERNMENT POWERS ENSURING LEGALITY, LAW ORDER, PROTECTING THE RIGHTS, FREEDOMS AND LEGITIMATE INTERESTS OF CITIZENS - Matviichuk, Andriy; Bagatko, Anastasia (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2024)
Purpose: to outline the current potential of the municipal police in the context of implementing the powers of executive bodies of local self-government to ensure legality, law and order, protection of the rights, freedoms and legitimate interests of citizens. Research methods: the authors used in particular, the analytical method, generalization and system in combination with an integrated approach. Results: it was established that at the theoretical level of the research, during the period of martial law, the issues of ensuring legality, law and order, protection of the rights, freedoms and legitimate interests of citizens in combination with extremely urgent tasks in the field of defense work appeared in a new light. Implementation of relevant powers requires certain mechanisms at the level of local self-government, which could become the institute of local (municipal) police. Discussion: the logic of the ongoing decentralization reform should facilitate the realization of the right of local self-government bodies to create internal administrative structures for the effective implementation of legally determined powers. Taking into account the foreign experience and the Ukrainian practice of building local (municipal) police institutes, the normative and legal design of such institutes is extremely relevant. A strong argument for this is the potential of municipal law enforcement institutions outlined in the work to perform tasks in the field of defense work. The article presents that municipal police units created by local self-government bodies could act as the organizational core of voluntary formations and national resistance in certain territories.